Investigation of action of pyrazole derivatives on plant growth and development in vivo and in vitro - Mohilnikova, I.V.; Tsygankova, V.A.; Gurenko, A.O.; Brovarets, V.S.; Bilko, N.М.; Yemets, А.І. (Reports of the National Academy of Sciences of Ukraine, 2021)
The action of synthetic low molecular weight compounds — pyrazole derivatives — on the growth and development of tomato plants (Solanum lycopersicum L.) of the Money Maker cultivar in vivo and in vitro is studied. It is found that the compound D-pyrazole-3 at a concentration of 10–8 М demonstrates the most pronounced action on the growth and development of tomato plants in vivo. The effect of these compounds on the morphogenetic potential of S. lycopersicum explants in vitro is studied for the first time, and it is found that compounds D-pyrazole-1, D-pyrazole-2 and D-pyrazole-3 effectively induce callusogenesis and rhizogenesis, as well as, depending on the concentration, direct plant regeneration in vitro. Under the action of all three compounds, both at a concentration of 10–9 М and 10–8 М, the most effective root formation occurs on shoot explants. For the direct plant regeneration from this type of explants, the most effective compounds are D-pyrazole-1 at a concentration of 10–9 М or D-pyrazole-2 at a concentration of 10–8 М, which can then be recommended for the use in the biotechnological research of the genetic improvement of S. lycopersicum.